Aktivitas Penumbuh Rambut Sediaan Hair Tonik Minyak Esensial Kayu Manis (Cinnamomum burmanii) and Minyak Kelapa - Heroweti, Junvidya; Wibowo, Danang Novianto; Khoeriyah, Himatul; Adelia, Ramadhania (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Cinnamaldehyde in cinnamon essential oil, lauric acid, myristic acid, and oleic acid in virgin coconut oil (VCO) were used in hair tonic preparations as hair growth agents. This study aimed to evaluate particle size and obtain optimum formulation of the hair tonic preparation and to observe growth activity with various levels of cinnamon essential oil and VCO. This research an experimental with rabbit used 4 test were divided into 6 treatment groups: 1) positive control (Regrou®); 2) normal control (without treatment); 3) negative control (hair tonic basis); 4) F1(1% cinnamon essential oil: 2.5% VCO); 5), F2 (3% cinnamon essential oil : 2.5% VCO); and 6), F3 (5% cinnamon essential oil: 2.5% VCO). The particle size analysis selected in formula 2 that cycle stable during storage, and fall into the microemulsion size range of 20-200 nm and there was no difference cycle because the significance was >0.05. The hair growth activity was determined using Average Growth Daily Gain.(AGD) formula and then.was analyzed.statistically using.One Way Anova. The results showed that had hair growth activity that was not significantly different. However, when compared with the positive control, formula 3 has hair growth activity above the positive control.